Analysis of Public Policy in Malang City Through Measurement of Environmental Pillar SDGs Indicators in the Perspective of Public Budgeting Allocation - Nusba Aini, Asfa Agustina; Rahmawati, Farida; Sumarsono, Hadi (IJBLE Scientific Publications Community Inc., 2023)
In the achievement of the Sustainable Development Goals, the efficient disbursement of allocated budgets is critical. Budgets are recognized as one of the most powerful tools available to administrations to encourage contributions, and therefore several initiatives have emerged to align budget items and Sustainable Development Goal performance. This research aims to know the effectiveness and efficiency of the implementation of the environmental pillar SDGs in Malang City and analyze budgeting allocation policies that are more effective efficient and sustainable for the implementation of environmental pillar SDGs indicators in Malang City. The result is the level of effectiveness of the implementation of the environmental pillar SDGs in Malang City occurred in 2022, while the efficiency of the implementation of the environmental pillar SDGs in Malang City also occurred in 2022 with an efficiency value of 15.04 percent. The best effectiveness achievement in 2022 was supported by goal 6: clean water and proper sanitation, goal 11: sustainable cities and settlements and goal 13: addressing climate change with a total of 23 indicators. The best efficiency in 2022 is supported by the number of efficiency numbers in goal 6: clean water and proper sanitation, goal 12: responsible consumption and production, and goal 15 terrestrial ecosystems. As for budgeting allocation that is more effective efficient and sustainable for the implementation of environmental pillar SDG indicators in Malang City, it can make 2022 the basic reference year. Especially in matters of program/activity implementation to achieve the goals of the environmental pillar SDGs